Light field analysis for modeling and transmission characteristics of partially coherent light-emitting diodes - Miao, Zhifang; Zhang, Pengfei; Lu, Fang; Han, Xiang’e; Li, Qiwei (Frontiers in Physics, 2023)
When analyzing the transmission characteristics of LEDs for long-distance lighting and communication applications, the light field is commonly assumed to be fully incoherent. However, in reality, the LED light source emits partially coherent light with a spatial coherence length on the order of microns. This paper is based on the generalized higher-order Lambert model of LEDs and aims to construct a Gaussian-Schell model for the LED beam (LED-GSM) on the near-field source plane, with a half-power angle of no more than 10^o. Utilizing the cross-spectral density function transmission theory for partially coherent light, this paper provides the LED-GSM model's spatial coherence length and beam radius at different distances and designs an experiment for measuring the spatial coherence length of LED beams. Experimental measurements of the spatial coherence length and beam spot size of LED beams at different distances are carried out using a Thorlabs LED528EHP light source. The experimental results match well with the theoretical simulations of the LED-GSM model, thus validating its effectiveness. Then, the proposed LED-GSM model is utilized to investigate the long-distance transmission characteristics of partially coherent narrow-beam LED light. Simulation results indicate that the spatial coherence length of the LED light field can reach tens to hundreds of millimeters over transmission distances of several kilometers. The beam radius is much smaller than that of the beam radius based on the fully incoherent model, and the beam intensity distribution also displays distinct differences.